Efektivitas Bantuan Langsung Tunai Pada Masa Pandemi Covid-19 Di Desa Langsepan Kecamatan Sumbersari (Studi Kasus Rt 03 Rw 18) - Nurussolah, Indrawan; Fawaid, Achmad (LAN TABUR : Jurnal Ekonomi Syariah, 2023)
Village Fund Direct Cash Assistance (BLT Dana Desa) is one of the actions taken by the government to provide subsidies to people in need in Indonesia. The aims of this study are: 1) Economic Conditions of Direct Cash Assistance (BLT Dana Desa) in RT 03 RW 18 Village Langsepan, Sumbersari District. 2) Mechanism for the distribution of Direct Village Fund Cash Assistance (BLT Dana Desa) to the community in RT 03 RW 18 Langsepan Village, Sumbersari District. This type of research uses qualitative research with a descriptive approach, determining research subjects using purposive sampling. Data collection techniques used interviews, observation, and documentation, the validity of the data in this study used technical triangulation. The results of this study indicate that: 1. Village Fund BLT recipients in Langsepan Village, Sumbersari District before the COVID-19 pandemic had an irregular income, but still can find a job to meet their daily needs. During the COVID-19 pandemic it hampered this in meeting economic needs so that the Village Fund BLT helped meet the basic needs of the community. 2. The mechanism for distributing Village Fund BLT in Langsepan Village, Sumbersari District, is carried out in cash every month for 9 months in the village office hall by complying with health protocols, in 3 stages/waves from April 2020 to December 2020 by implementing the accuracy of determining choice, target accuracy, timeliness, and program monitoring so that the distribution mechanism can be said to be effective. Keywords: Effectiveness of Direct Cash Assistance